Factors associated with the humanization of childbirth in a maternity hospital in the south of the state of Maranhão (Research, Society and Development, 2021)
Humanized Childbirth consists of a set of strategies that are adopted by the nursing team with other professionals that aims to provide the most comfortable and less painful parturition process for women. To identify factors associated with the humanization of care during labor, delivery and birth. This is a cross-sectional study of descriptive - exploratory and quantitative approach carried out at the Regional Maternal And Child Hospital of Imperatriz (HRMI) from October to December 2019. The research had the participation of 120 puerperal women of vaginal delivery aged between 18 and 41 years. The participants were mostly brown and with an income of up to 1 minimum wage. The vast majority considered that there was humanization in their delivery through the conducts adopted by the team. Regarding the application of non-pharmacological pain relief methods at the time of delivery, more than 60% of the participants reported having received this type of care, which indicates the adoption of humanized practices. Good practices of care in childbirth were found in this research according to the perception of postpartum women. The professionals promoted actions with the objective of making labor and delivery a more effective and less painful process. The conducts performed by the nursing team and shown in this study are principles for the adoption of humanized delivery, which provides women with a safer and more humane delivery contributing to maternal and child well-being.